Principles for transformative ocean governance - Lombard, Amanda; Clifford-Holmes, Jai; Goodall, Victoria; Snow, Bernadette; Truter, Hannah; Vrancken, Patrick; Jones, Peter; Cochrane, Kevern; Flannery, Wesley; Hicks, Christina; Gipperth, Lena; Allison, Edward (Eddie); et al. (Nature Research, 2023)
With a focus on oceans, we collaborated across ecological, social and legal disciplines to respond to the United Nations call for transformation in the ‘2030 Agenda for Sustainable Development’. We developed a set of 13 principles that strategically and critically connect transformative ocean research to transformative ocean governance (complementing the UN Decade for Ocean Science). We used a rigorous, iterative and transparent consensus-building approach to define the principles, which can interact in supporting, neutral or sometimes conflicting ways. We recommend that the principles could be applied as a comprehensive set and discuss how to learn from their interactions, particularly those that reveal hidden tensions. The principles can bring and keep together partnerships for innovative ocean action. This action must respond to the many calls to reform current ocean-use practices which are based on economic growth models that have perpetuated inequities and fuelled conflict and environmental decline.